The chemical composition of different leaf extracts of Lantana fucata Lindl. influences its cytotoxic potential: A study using the Allium cepa model. (10th May 2022) - Eckert, Giovana Laís; Smaniotto, Thiago Ângelo; Dartora, Nessana; Pelegrin, Carla Maria Garlet de; Baroni, Suzymeire
Abstract: Ethnopharmacological relevance: One of the most popular plants used to treat diseases in Brazil is Lantana fucata . Like most herbal medicines, its consumption is based on popular knowledge, which, despite being considered effective, may cause side effects. Aim of the study: Since the scientific data on the pharmacological properties of L. fucata are still incipient, this research aimed to evaluate the cytotoxic and genotoxic potential of different types of extracts (infusion, aqueous and hydroalcoholic), characterizing them chemically. Materials and methods: The cytotoxicity assay was performed by the A. cepa model. The cytotoxicity parameters studied were number of dividing cells and percentage mitotic index (%MI). Results: The result of the A. cepa assay showed that there was a decrease in the number of dividing cells and the percentage mitotic index as concentrations increased, for all extracts, indicating cytotoxicity. However, the hydroalcoholic extract was the most cytotoxic. Chromatography analysis allowed the characterization of secondary metabolites in the extracts, which were very similar. However, a greater abundance of flavonoids and triterpenoids was observed in the hydroalcoholic extract, suggesting that these compounds are responsible for its greater toxicity. Conclusions: Since the highest doses of extracts showed to have a cytotoxic effect, it is suggested that the ingestion of this species occurs in a moderate way. Graphical abstract: Image 1